Effect of the Chloride Anions on the Formation of Self-Assembled Diphenylalanine Peptide Nanotubes - Dayarian, Shima (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2018)
Self-assembled peptide nanostructures are being intensively investigated due to their potential applications such as biosensors, piezotransducers, and microactuators. It was predicted that their formation and hence piezoelectric property strongly depend on the water content and acidity of the stock solution. In this paper, simple diphenylalanine (FF) tubular structures were fabricated from the solutions with added hydrochloric acid in order to understand the influence of chloride ions on the self-assembly process and resulting piezoelectricity. Low-frequency Raman scattering, atomic, and piezoresponse force microscopies were used to characterize both the morphology and piezoelectric properties of the grown samples. The mechanism of chloride anions' effect on the formation of self-assembled peptide nanostructures is discussed based on the acquired Raman data and quantum-chemical modeling. It is shown that the addition of chloride anions causes a significant reduction of the dipole moments of FF tubes accompanied with the concomitant decrease of tube dimensions and apparent shear piezoelectric coefficients